Information Security and the Internet - Shamiloglu Kurbanov, Aiden; Romanovna Lenkovskaya, Renata; Viktorovna Lutovinova, Natalya; Efratovna Zolotareva, Alla; Valerievich Zhesterov, Pavel (International Journal of Engineering and Technology, 2018)
The article analyzes problems of poor legal regulation of relationships in the Internet when the network is used as a mean of information dissemination. The article focuses on the analysis of judgements in cases involving organizations that distribute software designed for maintenance of the companiesâ€™ paper flow, when such cases reveal evidences of non-licensed use of information. Gaps are identified in possibility to use civil methods of information protection traditional for the Russian system of justice. The authors found some inefficient information protection methods considering the level of processes and technology development, such as watermarks on the images, information depositing in Web-depository. The articles draw special attention to the requirements that an author and owner may put forward to information protection in the Internet.Â Â